Restructuring Labor and Employment (Political Aspects) - Siarova, Elka (Research Papers, 2018)
The paper present and systemize some political economic aspects of restructuring of the labour market and the employment climate in Bulgaria. The descriptive empiric analysis is based on interpretation and critical analysis of the essential theoretical concepts. The dynamic of the ongoing processes is provided in graphics, tables and diagrams in order to give comprehensive understanding of the running tendencies. In addition, it presents a comparative analysis, which outlines certain similarities and differences in the mentioned tendencies between Bulgaria and the EU.
Keywords: Knowledge economy; Labor market; Employment restructuring; Economic transformation